Microstructure and photocatalytic activities of thermal sprayed titanium dioxide/carbon nanotubes composite coatings - P. Daram (2018)
© 2016 This research aims to study the microstructure and photocatalytic performances of titanium dioxide/carbon nanotubes (TiO2/CNTs) composite coating. A TiO2/CNTs composite coating was prepared by plasma spraying from Ni catalytic nanoparticles supported on TiO2(rutile phase) particles which were prepared by an impregnation method. CNTs were synthesized on the TiO2/Ni powder from an ethanol atmosphere at 650 °C for 60 min by chemical vapor deposition technique. The pure TiO2and composite powders and their coatings were characterized by SEM, TEM, EDS, XRD, and UV–vis spectroscopy. The result shows that CNTs with a diameter of 50–130 nm were successfully grown in-situ on the surface of TiO2particles. The coatings mainly consisted of rutile-TiO2, while the Ni catalyst was found in the composite coating. It was found that the thickness and percentage of porosity of the composite coating were similar to those of pure coating. However, the efficiency in methylene blue decomposition of the composite coating was much higher than that of pure TiO2coating. The result demonstrates a new composite coating with a better photocatalytic performance compared to a pure rutile TiO2coating. It is expected that this composite coating can be further used for water pollutant applications.